Kontrastywizm epistemiczny - Palczewski, Rafał (Filozofia Nauki, 2009)
According to contrastivism in epistemology - advocated chiefly by Jonathan Schaffer - the knowledge relation is not binary (s knows that p) but ternary (s knows that p rather than q). Thus knowledge ascriptions are contrast-sensitive. The aim of this paper is to portray, investigate and assess the details of this view. In the first three sections I focus mainly on arguments for contrastivism. Section fourth is devoted to the contrastivist solution to the skeptical puzzle. In the last three sections I present several problems for contrastivism as well as three main binary explanations for contrast-sensitivity.